Time in M. Foucault’s Epistemological Configurations - Yu. L. Sirotkin (Дискурс)
Introduction. The article examines the concepts of time and space set forth in the works of M. Foucault, reveals their nature and Genesis. An analysis of the space-time continuum of historical retrospect in Foucault’s epistemological configurations is proposed. The interpretation of the French philosopher’s ideas is carried out in the vector of anthropological discourse. The article is free from nuance in the presentation of the revealed issues, which is the result of the specification of Foucault’s texts. The purpose of this article is to analyze the space-time continuum in the original interpretation of the famous French philosopher. The need for analysis is caused by the lack of domestic developments in space-time problems in the philosophical legacy of Foucault, who stood at the origins of post-non-classical knowledge and had a significant impact on the formation of the postmodern paradigm of space-time continuum analysis.Methodology and sources. The review of Foucault’s views on space-time is based on the author’s concept of the unity of man and the space-time continuum. We proceeded from the need for a human dimension of space-time, as well as from the fact that time-space is considered as an anthropological phenomenon. Our approach is based on the fact that the perception of the space-time continuum correlates with human changes. Time-space in Foucault’s epistemological configurations is analyzed in accordance with the initial ideas of the grounded concept.Results and discussion. The discourse of human dimensional space-time and its anthropological nature allows us to present Foucault’s views in a contradictory integrity and incorporate into it the often mutually exclusive messages that the philosopher formulated. The anthropological foundations of Analytics allow us to state the originality in the formulation of the time-space problem in Foucault’s cognitive models.Conclusion. The anthropological nature in the dimension of space-time Foucault was one of the foundations of anthropological approaches to the analysis of the space-time continuum in postnonclassical the evolution of French structuralism and post-modernist paradigm as a whole (Deleuze, Derrida, etc.).